High density lipoproteins of blood plasma as a transport form of actinomycin D - L. M. Polyakov; R. A. Knyazev; A. V. Ryabchenko; N. V. Trifonova; M. V. Kotova (Сибирский онкологический журнал)
Introduction. The development of new and highly effective antitumor therapy is one of the priorities of pharmacology. The paper presents one of the solutions to the problem related to the development of transport forms of antitumor drugs.The aim of the study was to study the ability of various fractions of plasma lipoproteins (VLDLP, LDL, HDL) to interact with actinomycin D and show the role of HDL as a transport form of actinomycin D in the body cells.Material and methods. The studies were conducted using unlabeled and tritium-labeled actinomycin D, preparative ultracentrifugation of the rat plasma lipoprotein fractions, chromatography, and in vivo experiments with intravenous administration of HDL complexes with labeled actinomycin D.Results. The important role of HDL in the formation of complexes with actinomycin D in comparison with LDL and LPA was shown. The basic physicochemical characteristics of the interaction of HDL and apolipoprotein A-I with actinomycin were obtained. The constants of the association were of the order of 105 M-1, and the number of binding sites for the drug was 26 for HDL and 12 for apolipoprotein A-I. In vivo studies on rats, the highest radioactivity after intravenous injection of HDL complexes with tritium-labelled actinomycin D was observed in the adrenal glands, then in the liver and kidneys. The uptake of tritium-labelled actinomycin D was twice lower in the lungs, adipose tissue, thymus and spleen. The low uptake of the label was observed in the myocardial tissue.Conclusion. The results obtained demonstrate the feasibility of using HDL as a transport form of actinomycin D in body cells.